The classification of the Masa group of languages - Aaron Shryock (LibraryPress@UF, 1997)
The Chadic family of languages comprises approximately 140 languages classified into three major branches: West Chadic, Biu-Mandara, and East Chadic. Newman [l977b] has proposed an additional, fourth branch of Chadic consisting of the Masa group of languages, previously classified in the Biu-Mandara branch. This article provides supporting evidence for Newman's classification of the Masa group as a fourth branch by demonstrating that this group does not exhibit the phonological, lexical, and morphological innovations characteristic of the BiuMandara branch. It follows from the absence of these innovations that there is no evidence for the classification of the Masa group in the Biu-Mandara branch.